EDUCATION AND TRAINING NEEDS IN ELECTRONIC RECORDS MANAGEMENT: A CASE STUDY OF RECORD KEEPERS IN THE MALAYSIAN FEDERAL MINISTRIES - Johare, Rusnah (Malaysian Journal of Library and Information Science, 2006)
This study examines the needs of record keepers in relation to knowledge and skills required to manage electronic records in the specific context of the Electronic Government (EG) in Malaysia. The research adopted a case study approach that combined both quantitative and qualitative data to answer the research questions. A questionnaire survey and in-depth interviews were used to investigate and identify the roles and responsibilities of different record keepers in the Malaysian Federal Ministries, explore the context in which the record keepers managed electronic records, and examine their needs for education and training in electronic records management (ERM). The study indicates the lack of knowledge and skills in ERM of the different record keepers.